Evaluation of Anti-Nociceptive and Anti-Inflammatory Activities of Apium graveolens L. Roots Extract in Mice - Ali Mohammad Ranjbar*; Alireza Vahidi; Mohammad Ebrahim Rezvani; Vahid Ramezani; Minoo Boroumand; Yadollah Jahani (Iranian Society of Pharmacognosy, 2019)
Background and objectives: Pain is an unpleasant feeling which affects the quality of life and relieving from pain is an important goal in many treatment protocols. Apium graveolens L. (celery) has been considered as sedative, analgesic, carminative, antispasmodic and diuretic in Iranian traditional medicine. The aim of present study was to evaluate the anti-nociceptive and anti-inflammatory effect of celery root in mice. Method: Repeated maceration was employed as extraction method. Hot plate and acetic acid writhing test were conducted to assess analgesic effect of celery root. The extract was also evaluated for anti-inflammatory probable effect by formalin induced ear edema and xylene induced paw edema tests. Results: Total flavonoid content determined by aluminum chloride colorimetric method was 0.0625 mg quercetin/g extract. No significant difference was observed between the positive control group which received morphine and test group in hot plate test and the most effective dose of celery root extract was 200 mg/kg, while the frequency of writhings was significantly different in all test groups in comparison with control group (p value< 0.05), the extract (100, 200 and 400 mg/kg) significantly suppressed inflammation in formalin induced edema assay, 60 and 120 min after injection. The results of xylene test also demonstrated notable antiedematogenic effect in applying 200 and 400 mg/kg of extract. Conclusion: Celery root has analgesic and anti-inflammatory effects which might be related to the flavonoids and resins present in the species.